2020
DOI: 10.3390/jcm9093055
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of, and Factors Associated with Prolonged Hospitalization: A Multicentre Study in Victoria, Australia

Abstract: Background: Limited available evidence suggests that a small proportion of inpatients undergo prolonged hospitalization and use a disproportionate number of bed days. Understanding the factors contributing to prolonged hospitalization may improve patient care and reduce the length of stay in such patients. Methods: We undertook a retrospective cohort study of adult (≥20 years) patients admitted for at least 24 h between 14 November 2016 and 14 November 2018 to hospitals in Victoria, Australia. Data including b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 46 publications
(114 reference statements)
4
21
0
Order By: Relevance
“…In comparison to the aforementioned data, the risks for VRE colonization found in our study are high. Ofori-Asenso et al [ 48 ] found older age and level of comorbidity as factors independently associated with prolonged hospitalization. Additionally, the risk of HAIs increased with the prolonged hospitalization, but at the same time HAIs increase the duration of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to the aforementioned data, the risks for VRE colonization found in our study are high. Ofori-Asenso et al [ 48 ] found older age and level of comorbidity as factors independently associated with prolonged hospitalization. Additionally, the risk of HAIs increased with the prolonged hospitalization, but at the same time HAIs increase the duration of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Factors independently associated with prolonged hospitalization included age, female gender, admission from another hospital, admission on the weekend, and the number of admissions in the prior 12 months. They found that patients admitted for surgical reasons were less likely to experience prolonged hospital stay compared to medical admissions [14]. The average LOS in some studies was 13.7 ± 8.9 days.…”
Section: Literaturementioning
confidence: 99%
“…Numerous studies on ELOHS have described ELOHS as a specific number of days in the hospital that corresponds to the 75th percentile of the studied cohorts [ 9 , 16 , 21 ] while others chose a particular number of days in the hospital as the limit for NLOHS for a combination of DRGs [ 30 , 31 , 35 ]. Unfortunately, the variability in the severity of health conditions with various DRGs makes it imperative to consider ELOHS as a DRG-specific definition requiring specific durations.…”
Section: Introductionmentioning
confidence: 99%